Changes in selection regime cause loss of phenotypic plasticity in planktonic freshwater copepods - Sereda, Sergej Vitalevic; Wilke, Thomas; Schultheiß, Roland; Justus Liebig University Giessen (My University, 2014)
Rapid phenotypic adaptation is critical for populations facing environmental changes and can be facilitated by phenotypic plasticity in the selected traits. Whereas recurrent environmental fluctuations can favour the maintenance or de novo evolution of plasticity, strong selection is hypothesized to decrease plasticity or even fix the trait (genetic assimilation). Despite advances in the theoretical understanding of the impact of plasticity on diversification processes, comparatively little empirical data of populations undergoing diversification mediated by plasticity are available. Here we use the planktonic freshwater copepod Acanthodiaptomus denticornis from two lakes as model system to study UV stress responses of two phenotypically different populations under laboratory conditions. Our study reveals heritable lake- and sex-specific differences of behaviour, physiological plasticity, and mortality. We discuss specific selective scenarios causing these differences and argue that phenotypic plasticity will be higher when selection pressure is moderate, but will decrease or even be lost under stronger pressure.
Keywords: ddc:570